DETERMINATION OF THE LUNDAYEH DAYAK COMMUNITY CULTIVATION CALENDAR: ETHNOASTRONOMICAL MODELING - oktrivia, ulce; Hindarto, Imam; Bawono, Rochtri Agung; Herwanto, Eko; Oktaby, Naurus Zaman; Karma, Made Prarabda; Darma, I Kadek Sudana Wira Darma (BRIN, 2024)
Traditional ecological knowledge and planting time management have led to agricultural success in Krayan. The Lundayeh community in Krayan determines planting time based on sun’s position as seen from a sign stone. The problem in this study is in what month do farming activities begin if determined based on sun’s position? This study aims to reconstruct the local knowledge of the Lundayeh community. Data collection was conducted by surveys, interviews, and measuring the azimuthal angle from the observation location to the position of the sun. To observe the position of the sun one has to stand on a marker stone and direct the view to the sunset location marker. At the Long Mutan marker stone, the sunset location markers are two hills, Tudal Wir and An Lam. When the sun sets over Tudal Wir Hill, the slash-and-burn process begins, which is around 11 May and 3 August. The activity of spreading seedlings will start when the sun sets over An Lam Hill, which is around 20 September.